Association between household cooking energy sources and under-five mortality: evidence from demographic health survey - Byrne Kaulu; Eskaya Martha Kapilili; Paul Kaulu; Goodwell Kaulu (Egyptian Pediatric Association Gazette)
Abstract Background The primary objective of this study is to assess the association between household cooking energy sources and under-five mortality. This is significant because it informs public health interventions and policies for clean cooking sources and improved child health. It uses weighted logistic regression to assess the association of various cooking energy sources with under-five mortality. The data consists of 38,446 survey responses from the 2018 demographic health survey, Zambia dataset. The dependent variable was measured as a binary outcome with 1 being no under-five mortality has ever occurred in the household and 0 being at least one such mortality has occurred. The regressors were cooking fuel choices, access to health care, mother’s education, wealth index and child spacing. Binary coding was used to measure access to healthcare and child spacing. Mother’s education was categorized into; no education, incomplete primary, complete primary, incomplete secondary, complete secondary, and higher education. The DHS wealth index showed the poorest, poorer, richer, and richest households. All the fuel choices in the DHS dataset were adopted without modification. Results A child in a household using charcoal cooking fuel is at least 1.58 times more likely to experience under-five mortality than one using electricity (OR = 1.58, 95% CI = 1.09—2.29). Neither distance to a health facility (OR = 0.98, 95% CI = 0.84—1.14) nor access to money for health services (OR = 1.057, 95% CI = 0.89—1.26) had significant association with under-five mortality. A child whose mother has secondary education or higher is at least 0.38 times less likely to experience under-five mortality compared to one with no education (OR 0.62, 95% CI = 0.42—0.92). Being from the richest households had lower odds (OR = 0.53, 95% CI = 0.38—0.73) of under-five mortality than being from poorest households. Conclusions Based on the above, we recommend various energy, health and community development policies, practices and scholarly directions. We recommend inter alia; energy transition, subsidies for communities who comply, comprehensive education and investment in health infrastructure. We further note the limitations of the study.